Coronavirus Crisis and Housing Policy Challenges - Holger Cischinsky; Philipp Deschermeier; Max-Christopher Krapp; Martin Vaché (Wirtschaftsdienst)
Abstract The coronavirus pandemic and the associated containment measures are likely to have serious effects on housing. In the short term, the German Federal Government has reacted with temporary exemptions for subject-oriented instruments as well as for rental and lending regulations. However, it has become apparent that further temporary regulations are needed within the scope of social security of housing. In the course of the recession, pronounced price declines on the housing markets are to be expected due to the great relevance of demandside developments. However, longterm labour migration will potentially revise the price declines. Housing policymakers would therefore be advised to stabilise housing construction activities or to orient them countercyclically in order to be able to cover longterm housing needs that will emerge by resurgent immigration.